Advances in Parvovirus Research 2022 (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Viruses in the Parvoviridae family constitutes a most diverse and intriguing field of research. Parvoviruses have a long evolutionary history and, beneath an apparent simplicity and uniformity, can differ widely in structure, genome organization and expression, virus–cell interaction, and impact on the host. In addition to interest in the study of basic virology, the translational implications of research on parvoviruses are relevant since many viruses are important human and veterinary pathogens, while other viruses can be engineered as tools for oncolytic therapy or as sophisticated gene delivery vectors. Exploring the diversity and the inherent complexity in the biology of these apparently simple viruses is an ongoing commitment for the scientific community to address. This Special Issue entitled ‘Advances in Parvovirus Research 2022’ continued the series dedicated to research on viruses belonging to the Parvoviridae family and collected the latest contributions in the field of parvovirus research.